2001
DOI: 10.1074/jbc.m103148200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Escherichia coli MutS and MutL at a DNA Mismatch

Abstract: MutS and MutL are both required to activate downstream events in DNA mismatch repair. We examined the rate of dissociation of MutS from a mismatch using linear heteroduplex DNAs or heteroduplexes blocked at one or both ends by four-way DNA junctions in the presence and absence of MutL. In the presence of ATP, dissociation of MutS from linear heteroduplexes or heteroduplexes blocked at only one end occurs within 15 s. When both duplex ends are blocked, MutS remains associated with the DNA in complexes with half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
159
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(177 citation statements)
references
References 38 publications
(47 reference statements)
15
159
1
Order By: Relevance
“…In addition, DNasel footprinting studies reveal that whereas MutS protects approximately one turn of the DNA helix to either side of the mismatch consistent with the crystal structures, the MutS-MutL interaction in the presence of ATP yields a very large DNasel footprint indicative of multiple proteins bound to the DNA (Grilley et al, 1989;Selmane et al, 2003). Formation of a ternary complex involving either the E. coli or human MMR proteins also requires DNA heteroduplexes in excess of 60 bp reflecting multiple binding events in vitro (Blackwell et al, 2001;Plotz et al, 2002;Schofield et al, 2001b). Whether this is an artefact of in vitro conditions or reflects multiple loadings of MMR proteins, either multiple loading of diffusing clamps or cooperative binding of a protein filament, is not definitively established.…”
Section: A Ternary Complexmentioning
confidence: 73%
“…In addition, DNasel footprinting studies reveal that whereas MutS protects approximately one turn of the DNA helix to either side of the mismatch consistent with the crystal structures, the MutS-MutL interaction in the presence of ATP yields a very large DNasel footprint indicative of multiple proteins bound to the DNA (Grilley et al, 1989;Selmane et al, 2003). Formation of a ternary complex involving either the E. coli or human MMR proteins also requires DNA heteroduplexes in excess of 60 bp reflecting multiple binding events in vitro (Blackwell et al, 2001;Plotz et al, 2002;Schofield et al, 2001b). Whether this is an artefact of in vitro conditions or reflects multiple loadings of MMR proteins, either multiple loading of diffusing clamps or cooperative binding of a protein filament, is not definitively established.…”
Section: A Ternary Complexmentioning
confidence: 73%
“…Several research groups have reported an apparent reduction in the affinity of MutS for mismatched DNA following ATP binding, which manifests as MutS sliding off short linear mismatched DNA substrates with unblocked ends during gel mobility-shift analysis (1,13,(23)(24)(25)28,48); presumably, such movement of MutS on DNA serves an important function during mismatch repair. Since we have now identified some nucleotide-bound forms of MutS in the pathway, we tested their interaction with +T-containing duplex DNA substrate.…”
Section: What Is Their Function?mentioning
confidence: 99%
“…ATP binding and hydrolysis appear to modulate the interactions between MutS/Msh and DNA as well as other proteins in the repair pathway; thus, understanding how MutS/Msh proteins utilize ATP is necessary for understanding how they function in DNA mismatch repair. Several model mechanisms have been proposed for MutS/Msh action upon mismatch recognition: (a) MutS/Msh proteins translocate on DNA, fuelled by ATP binding and hydrolysis, possibly to interact with other proteins on DNA and coordinate mismatch recognition with downstream events such as initiation of strand excision and DNA resynthesis [8][9][10]; (b) upon binding ATP MutS/Msh proteins form sliding clamps that diffuse freely on DNA, again, to contact downstream repair proteins and direct repair [11,12]; (c) MutS/Msh proteins utilize ATP binding and hydrolysis to modulate their interaction with DNA, while remaining at the mismatch to direct repair [13][14][15][16][17]. At present, experimental data are available in support of each of these very different model mechanisms, therefore the investigation into MutS/Msh DNA binding and ATPase activities continues.…”
Section: Introductionmentioning
confidence: 99%